Student reporting abroad: An international programme called Journalism Reporting Field Trips - Lee Duffield (Asia Pacific Network, 2008)
A programme organised by the author for journalism students to do practical work overseas has seen small groups engaged in intercultural learning and working as foreign correspondents for campus-based media outlets. Since 2000, 60 students have joined nine tours of 10–20 days in nine countries of Europe and the Asia-Pacific region. They obtain credit for a full elective subject, e.g. an individual study unit, and may negotiate additional credits.